Propagating the Rosary in the Early Qing—A Case Study of del Rosario’s Comprehensive Manuscript - Yang, Hongfan (Religions, 2024)
Studies on the Rosary in the late Ming and early Qing usually focus on works written by Jesuits and mostly stem from an artistic aspect. This article, however, shifts the focus to The True Peace of Humankind, a manuscript written by the Dominican missionary Arcadio del Rosario in the seventeenth century, the first comprehensive book on the Rosary in Chinese. It first summarizes the early-stage propagation of the Rosary in China by the Jesuits and then examines the structure and content of The True Peace of Humankind. It is noteworthy that the manuscript repeatedly uses an analogy with flowers to highlight Mary’s intercession. Dating back to the Catholic tradition in Europe, the propagation of the Rosary through analogy with flowers resembles the propagation of reciting Buddhist prayers in Chinese society. This article applies contextual studies to explore two main questions: how is del Rosario’s manuscript different from the previous texts on the Rosary written by the Jesuits? What is the significance of the manuscript in the context of the Chinese Rites Controversy?